2017
DOI: 10.1111/pim.12440
|View full text |Cite
|
Sign up to set email alerts
|

IgE sensitization to Anisakis pegreffii in Italy: Comparison of two methods for the diagnosis of allergic anisakiasis

Abstract: IgE sensitization to Anisakis pegreffii in Italian subjects suffering from gastro-allergic anisakiasis (GAA) (N=5), or showing chronic urticaria (CU+) after fish consumption (N=100), was investigated. A control group (N=5) was also included. IgE response was analysed by immunoblotting (WB) assay, using both excretory/secretory products (ESPs) and crude extract (CE) of A. pegreffii larvae. The results were compared with those achieved by the conventional immunological method for Anisakis allergy (ie, immunoCAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Recently, the C‐type lectin receptors, recognizing carbohydrate ligands, seem to play a key role in triggering immunosuppressive functions of DCs by helminths . Interestingly, Ani s 7, among the major allergens in A. pegreffii , is indeed a glycoprotein …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the C‐type lectin receptors, recognizing carbohydrate ligands, seem to play a key role in triggering immunosuppressive functions of DCs by helminths . Interestingly, Ani s 7, among the major allergens in A. pegreffii , is indeed a glycoprotein …”
Section: Discussionmentioning
confidence: 99%
“…Among these, Anisakis simplex (sensu stricto ) and Anisakis pegreffii are shown to play a zoonotic role in humans . Anisakis pegreffii infection can provoke gastric (GA), intestinal (IA) and gastroallergic anisakiasis (GAA) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans can acquire an accidental infection with A. pegreffii mainly through consumption of raw, marinated, or undercooked fish fillets (mainly anchovies in Mediterranean countries) infected by the third stage larvae of this parasite (reviewed in [25,43]). Several cases of anisakiasis, due to the species A. pegreffii, have been reported in Italy [20,22,25,37,38,[41][42][43], Croatia [47], Japan [60] and South Korea [33]. These geographical areas, where human anisakiasis due to A. pegreffii has been described, correspond to areas where a high rate of parasite infection has been reported in commercial fish species [43].…”
Section: Introductionmentioning
confidence: 95%
“…and its antigens are the activation of Th2, leading to the secretion of cytokines, including interleukin (IL)-4, IL-5, IL-9 and IL-13 cells, which promote mast cell hyperplasia and eosinophilia. A recent study of Mattiucci et al [11] has shown that Ani s 7-like and Ani s 13-like, detected in the sera samples, could be considered as major antigens in the diagnosis of allergic anisakiasis caused by A. pegreffii.…”
Section: Introductionmentioning
confidence: 99%